High- density lipoprotein function is abnormal in idiopathic inflammatory myopathies. (24th August 2020) - Bae, Sangmae Sharon; Lee, Yuen Yin; Shahbazian, Ani; Wang, Jennifer; Meriwether, David; Golub, Ilana; Oganesian, Buzand; Dowd, Tyler; Reddy, Srinivasa T; Charles-Schoeman, Christina
Abstract: Objective: Damage to the vascular endothelium is strongly implicated in the pathogenesis of idiopathic inflammatory myopathies (IIM). Normally, high‐density lipoprotein (HDL) protects the vascular endothelium from damage from oxidized phospholipids, which accumulate under conditions of oxidative stress. The current work evaluated the antioxidant function of HDL in IIM patients. Methods: HDL's antioxidant function was measured in IIM patients using a cell-free assay, which assesses the ability of isolated patient HDL to inhibit oxidation of low-density lipoproteins and is reported as the HDL inflammatory index (HII). Cholesterol profiles were measured for all patients, and subgroup analysis included assessment of oxidized fatty acids in HDL and plasma MPO activity. A subgroup of IIM patients was compared with healthy controls. Results: The antioxidant function of HDL was significantly worse in patients with IIM ( n  = 95) compared with healthy controls ( n  = 41) [mean (S.d .) HII 1.12 (0.61) vs 0.82 (0.13), P  < 0.0001]. Higher HII associated with higher plasma MPO activity [mean (S.d .) 13.2 (9.1) vs 9.1 (4.6), P  = 0.0006] and higher oxidized fatty acids in HDL. Higher 5-hydroxyeicosatetraenoic acid in HDL correlated with worse diffusion capacity in patients with interstitial lung disease ( r  = −0.58, P  = 0.02), and HDL's antioxidant function was most impaired in patients with autoantibodies against melanoma differentiation-associated protein 5 (MDA5) or anti-synthetase antibodies. In multivariate analysis including 182 IIM patients, higher HII was associated with higher disease activity and DM diagnosis. Conclusion: The antioxidant function of HDL is abnormal in IIM patients and may warrant further investigation for its role in propagating microvascular inflammation and damage in this patient population.